The Principles of Internalization of Qawlan Ma'rufa Perspective of the Quran and it’s Relevance to Ethics Contemporary Communication - Khairuddin, Khairuddin; Husin, Husin; Usman, Usman; Muhlasin, Muhlasin; Romadi, Pipir (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This article aims to explain the principles of qaulan ma'rufa which is one of the principles of communication found in the Qur’an. This aims to answer the public's anxiety where there is often a lack of ethics in someone's communication. This research belongs to library research, namely library research, because all of the primary data is written data, especially related to the verses of the Qur’an about the principles of qawlan ma'rufa and their internalization of contemporary communication. The main source is the Qur’an. Also displayed are sources from the hadiths of the Prophet that are related to research where there are also hadiths of the Prophet related to the research. The results of this study indicate that the principles of qaulan ma'rufa as a form of communication that bring benefit to the community must be internalized in the life of the community itself, especially since these principles are part of Islamic teachings.